Доброзичлива вимогливість педагогіки - Пономарьов, Олександр Семенович (НТУ "ХПІ", 2016)
Сучасна парадигма вищої освіти ґрунтується на подоланні авторитарної педагогіки, на переході до бінарного характеру навчально-виховного процесу й демократизації взаємовідносин між педагогом і студентами. Ускладнення, зумовлені прискоренням науково-технічного прогресу, підвищують вимоги до якості підготовки фахівців і розвитку їх професійно значущих особистісних якостей. Для успішного розв’язання цих завдань необхідне поєднання доброзичливого ставлення до студентів з вимогливістю як прояв відповідального ставлення педагога до своєї діяльності. Завдяки доброзичливій вимогливості стає можливим забезпечити бажану ефективність навчання і виховання студентів.

The modern paradigm of higher education is based on overcoming authoritarian pedagogy, at the transition to the binary nature of the educational process and democratization of the relationship between teacher and students. Gaining ideas of good pedagogy. Complications due to the acceleration of scientific and technological progress, increased demands on the quality of training and the development of professionally significant personal qualities. It is sometimes necessary to overcome laziness and irresponsibility of students, help them understand the importance of training and discipline. To successfully meet these challenges, you must connect friendly to students with demanding as the manifestation of the teacher responsible attitude to their work. Benevolent demands makes it possible to ensure the desired effectiveness of the training and education of students, preparing them for a successful life and business activity.
Friendly demanding of the pedagogics
Keywords: вища освіта; педагогіка добра; взаємовідносини; професійна підготовка; відповідальність; higher education; pedagogics of good; relationships; professional training